Bumiputera's non-performing loans (NPLs) : a case study of Sarawak economic development corporation, (SEDC Sarawak) - Lingan, Insor (Universiti Malaysia Sarawak, 2004)
The study focuses on the managerial deficiencies, financial factors, and the personal attributes and degree of each of these factors in contributing to the financial stress that led to the financial failures of the Bumiputera participants in the two selected schemes, namely the Small Scale Enterpises (SSEs) and the Small Scale Industry Loan Scheme (SPIKS)